(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Data on the epidemiology of mastopathy and breast cancer, population risks of breast cancer, causes predisposing to mastopathy, and risk factors for breast cancer are presented .According to the literature, the process of "rejuvenation" of breast cancer over the past decades has seen an increase in this disease among women at a younger age under 40 years [1]. In addition, breast cancer in young women may have a worse prognosis and more aggressive biological behavior than breast cancer in elderly patients approx. Previous studies have shown that in young women, breast cancer is diagnosed at a later stage, characterized by high proliferative activity, low differentiated Oh, with estrogen receptor negative tumors, with the presence of asular invasion lymphs [7; 10]. Previously, the definition of "young women" included patients under 35 years of age, since 2015, the World Health Organization has developed a new age classification [12], according to which: persons under the age of 44 are young; 46-59 years old - to mature; 61-74 years old to the elderly; 75-90 years old - to the elderly. The threshold of longevity is considered to be the achievement of 90 years or more.